I wrote this code for mutipicate two polynomials but I want change it as it can get two polynomials and then multicipate them
for example:
input:
5x -2x^2 +x -1
-4 -2x
output:
4x^3 -4x^2 -22x +4

public class Polynomial{

public int[b+1];
        coef[b] = a;
        deg = degree();
    }

    // return the degree of this polynomial (0 for the zero polynomial)
    public int degree() {
        int d = 0;
        for (int i = 0; i < coef.length; i++)
            if (coef[i] != 0) d = i;
        return d;
    }

    // return c = a + b
    public Polynomial plus(Polynomial b) {
        Polynomial a = this;
        Polynomial c = new Polynomial(0, Math.max(a.deg, b.deg));
        for (int i = 0; i <= a.deg; i++) c.coef[i] += a.coef[i];
        for (int i = 0; i <= b.deg; i++) c.coef[i] += b.coef[i];
        c.deg = c.degree();
        return c;
    }

    // return (a - b)
    public Polynomial minus(Polynomial b) {
        Polynomial a = this;
        Polynomial c = new Polynomial(0, Math.max(a.deg, b.deg));
        for (int i = 0; i <= a.deg; i++) c.coef[i] += a.coef[i];
        for (int i = 0; i <= b.deg; i++) c.coef[i] -= b.coef[i];
        c.deg = c.degree();
        return c;
    }

    // return (a * b)
    public Polynomial times(Polynomial b) {
        Polynomial a = this;
        Polynomial c = new Polynomial(0, a.deg + b.deg);
        for (int i = 0; i <= a.deg; i++)
            for (int j = 0; j <= b.deg; j++)
                c.coef[i+j] += (a.coef[i] * b.coef[j]);
        c.deg = c.degree();
        return c;
    }





    // use Horner's method to compute and return the polynomial evaluated at x
    public int evaluate(int x) {
        int p = 0;
        for (int i = deg; i >= 0; i--)
            p = coef[i] + (x * p);
        return p;
    }

    // convert to string representation
    public String toString() {
        if (deg ==  0) return "" + coef[0];
        if (deg ==  1) return coef[1] + "x + " + coef[0];
        String s = coef[deg] + "x^" + deg;
        for (int i = deg-1; i >= 0; i--) {
            if      (coef[i] == 0) continue;
            else if (coef[i]  > 0) s = s + " + " + ( coef[i]);
            else if (coef[i]  < 0) s = s + " - " + (-coef[i]);
            if      (i == 1) s = s + "x";
            else if (i >  1) s = s + "x^" + i;
        }
        return s;
    }

    // test client
    public static void main(String[] args) { 
        Polynomial zero = new Polynomial(0, 0);

        Polynomial p1   = new Polynomial(4, 3);
        Polynomial p2   = new Polynomial(3, 2);
        Polynomial p3   = new Polynomial(1, 0);
        Polynomial p4   = new Polynomial(2, 1);
        Polynomial p    = p1.plus(p2).plus(p3).plus(p4);   // 4x^3 + 3x^2 + 1

        Polynomial q1   = new Polynomial(3, 2);
        Polynomial q2   = new Polynomial(5, 0);
        Polynomial q    = q1.plus(q2);                     // 3x^2 + 5



        Polynomial s    = p.times(q);



        System.out.println("p(x) =        " + p);
        System.out.println("q(x) =        " + q);

        System.out.println("p(x) * q(x) = " + s);
        System.out.println("p(q(x))     = " + t);

      }

}
Comments
fraudulent homework kiddo

I wrote this code for mutipicate two polynomials

LOL good one. I wrote that code. Check my username under my snippets. And it is an example in C++.

This article has been dead for over six months. Start a new discussion instead.